Structural and Energetic Insights Into the Interaction of Niacin With the GPR109A Receptor - Kiran Kumar Adepu (SAGE Publishing, 2021)
The transmembrane G-protein coupled receptor GPR109A has been previously shown to function as a receptor for niacin in mediating antilipolytic effects. Although administration of high doses of niacin has shown beneficial effects on lipid metabolism, however, it is often accompanied by disturbing side effects such as flushing, liver damage, glucose intolerance, or gastrointestinal problems. Thus, it is important to understand niacin-GPR109A interactions, which can be beneficial for the development of alternate drugs having antilipolytic effects with less or no side effects. To get into the structural insights on niacin binding to GPR109A, we have performed 100 nanoseconds long all-atom MD simulations of five niacin-GPR109A complexes (automatically docked pose 0, and randomly placed niacin in poses 1 to 4 in the receptor crevice) and analyzed using binding free energy calculations and H-bond analysis. Steered MD simulations were used to get an average force for niacin translocation between the bulk and the external crevice of the wild type and mutant (N86Y, W91 S, S178I, and triple mutant of all three residues) GPR109A receptors, as well as GPR109B (as a control that does not bind niacin). The H-bond analysis revealed that TMH3 residue R111 interacts with niacin in a total of 4 (poses 0 to 3) complexes, while residues C177, S178, and S179 contact niacin in complex pose 4, and all these complexes were energetically stable. According to steered MD simulations, all the GPR109A mutants and GPR109B required greater force than that of wild-type GPR109A to translocate in the external crevice, suggesting increased sterical obstacles. Thus, the residues N86 (at the junction of TMH2/ECL2), W91 (ECL2), R111 (TMH3), and ECL3 residues (C177, S178, S179) play an important role for optimal routing of niacin entry and to bind GPR109A.